Respuesta :
Answer:(3,0) , (-2,0)
Step-by-step explanation:To find the x-intercept, substitute in 0 for y and solve for x
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
[tex]f(x) = {x}^{2} - x - 6 [/tex]
[tex]f(x) = (x - 3)(x + 2)[/tex]
[tex]0 = (x - 3)(x + 2)[/tex]
_________________________________
Hint :
[tex]a \times b = 0[/tex]
[tex]a = 0 \: \: \: or \: \: \: b = 0[/tex]
_________________________________
Thus ;
[tex] x - 3 = 0[/tex]
Add sides 3
[tex]x - 3 + 3 = 0 + 3[/tex]
[tex]x = 3[/tex]
Or
[tex]x + 2 = 0[/tex]
Subtract sides 2
[tex]x + 2 - 2 = 0 - 2[/tex]
[tex]x = - 2[/tex]
Thus the x-intercepts are (( - 2 )) and (( 3 )) .
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️